Sequência de atividades para o ensino de energia e suas transformações, baseada em princípios facilitadores da aprendizagem significativa crítica - (:unkn) unknown (Universidade Federal do Pampa, 2018)
This work consists of elaborating, implementing and evaluating a sequence of activities on energy and its transformations, in which were addressed the concepts of energy, energy transformation, electric energy consumption and some sources of renewable and non-renewable energy. It aimed to understand the processes of teaching and learning about energy and its transformations in a 3rd grade group from a public school in Alegrete. Activities were designed, developed and performed in accordance with the Critical Significant Learning Theory (CSLT). The sequence of activities took in consideration, considered several types of students’ knowledge; It approaches the importance of planning serial activities, put it in a significant sequence to the students; and it is composed of experiments, simulations and a didactic game, aiming to provide the access to knowledge in a pleasant and funny way, allowing to associate learning with amusement. This way, this paper aimed to analyze if the activities, in the way they were presented, really smooth learning the subject, sear simulations and a didactic game with the purpose of providing access to knowledge in a pleasant and an enjoyable way. This way, it makes possible students to connect learning to satisfaction, turning easier the learning process. The evaluation of the work was qualitative, and it was carried out through rubrics. During the activities, it was observed that the students were motivated. The teaching and learning processes improved, and the students became more involved in the classroom activities. They were able to negotiate meanings, elaborate questions and discuss about the contents. The results show that the learning purposes based on the eleven facilitating principles were achieved with the application of the sequence of activities. The students were able to recognize the concept of energy and the relation among energies. Moreover, they understood the transformations suffered by the energy and demonstrated skills to make the calculation of the consumption of electric energy.
Keywords: Energia; Ensino-aprendizagem; Aprendizagem significativa crítica; Energy; Teaching- learning; Critical significant learning; CNPQ::CIENCIAS EXATAS E DA TERRA